A Three‐Dimensional Model of Pluto's Interaction With the Solar Wind During the New Horizons Encounter. Issue 10 (21st October 2017) - Feyerabend, Moritz; Liuzzo, Lucas; Simon, Sven; Motschmann, Uwe
Abstract: We apply a hybrid (kinetic ions and fluid electrons) simulation model to study Pluto's plasma environment during the New Horizons encounter on 14 July 2015. We show that Pluto's plasma interaction is dominated by significant north‐south asymmetries, driven by large pickup ion gyroradii on the order of 200 Pluto radii. The transition region from the ambient solar wind to the population of plutogenic ions (called the "Plutopause") also shows considerable asymmetries that cannot be explained by a fluid picture. Since the New Horizons spacecraft does not carry a magnetometer, we use our model to estimate the strength and direction of the interplanetary magnetic field (IMF) at the time of the flyby by comparing output from the hybrid simulation to the plasma signatures observed during the New Horizons encounter. We find that an IMF strength of at least 0.24 nT is required to generate the observed plasma signatures. An IMF orientation either parallel or antiparallel to Pluto's orbital motion is able to explain the observed plasma densities and velocities along the New Horizons trajectory. Our simulations are able to quantitatively reproduce all key features of the plasma observations, specifically the gradual slowing of the solar wind, as well as the location and thickness of the Plutopause and bow shock. Key Points: We provide a three‐dimensional model of Pluto's plasma environment during the New Horizons encounter Pluto's flat pickup tail is shaped by the significant asymmetries induced by large ion gyroradii A strong interplanetary magnetic field is required to explain New Horizons plasma data